A Rat Model of Human Lipid Emulsion Digestion - Steingoetter, Andreas; Arnold, Myrtha; Scheuble, Nathalie; Fedele, Shahana; Bertsch, Pascal; Liu, Dian; Parker, Helen L.; Langhans, Wolfgang; Fischer, Peter (Frontiers in Nutrition, 2019)
A better understanding of how dietary lipids are processed by the human body is necessary to allow for the control of satiation and energy intake by tailored lipid systems. To examine whether rats are a valid model of human dietary lipid processing and therefore useful for further mechanistic studies in this context, we tested in rats three lipid emulsions of different stability, which alter satiety responses in humans. Different sets of 15 adult male Sprague Dawley rats, equipped with gastric catheters alone or combined with hepatic portal vein (HPV) and vena cava (VC) catheters were maintained on a medium-fat diet and adapted to an 8 h deprivation/16 h feeding schedule. Experiments were performed in a randomized cross-over study design. After gastric infusion of the lipid emulsions, we assessed gastric emptying by the paracetamol absorption test and recorded in separate experiments food intake and plasma levels of gastrointestinal hormones and metabolites in the HPV. For an acid stable emulsion, slower gastric emptying and an enhanced release of satiating gastrointestinal (GI) hormones were observed and were associated with lower short-term energy intake in rats and less hunger in humans, respectively. The magnitude of hormonal responses was related to the acid stability and redispersibility of the emulsions and thus seems to depend on the availability of lipids for digestion. Plasma metabolite levels were unaffected by the emulsion induced changes in lipolysis. The results support that structured lipid systems are digested similarly in rats and humans. Thus unstable emulsions undergo the same intragastric destabilization in both species, i.e., increased droplet size and creaming. This work establishes the rat as a viable animal model for in vivo studies on the control of satiation and energy intake by tailored lipid systems.